GENERALIZED VARIATIONAL PROCEDURE: AN APPLICATION TO NONPERTURBATIVE QCD - CIVITARESE, O.; HESS, P. O.; AMOR-QUIROZ, D. A. (International journal of modern physics. E, Nuclear physics, 2013)
We present a generalized variational procedure oriented to the algebraic solution of many-body Hamiltonians expressed in bosonic and fermionic variables. The method specializes in the nonperturbative regime of the solutions. As an example, we focus on the application of the method to nonperturbative QCD.